Assessment of body composition, physical-sports practice and diet in high school students (Agora for Physical Education and Sport, 2020)
This study aims to analyze body composition, the weekly physical-sports practice and nutritional habits in secondary school students. Sixty subjects (1.57 ± 0.07 m; 49.4 ± 10.5 kg), aged between 12 and 13 participated in this cross-sectional descriptive study. Body composition, weekly hours of physical-sports practice and nutritional intake were evaluated. It was differences between gender in the abdominal fold, thigh fold, biepicondyloid diameter, percentage fat, percentage muscle and fat weight (p
Keywords: health; teenagers; nutrition